Microstructure and mechanical properties of high strength, low alloy steel via additive manufacturing - Chin, Clement Wen Jie (2018)
Additive Manufacturing (AM), otherwise known as 3D printing, is rapidly increasing in popularity in the manufacturing industry due to the advantages it provides as compared to conventional manufacturing techniques, helping manufacturers to save on both time and money. There are plenty of AM techniques available for manufacturers to adopt and use depending on the starting material phase (powder, solid, liquid). In this project, the material in question is A131 EH36, a type of low carbon steel suitable for use in the marine and offshore industry. The AM technique used would be the Laser Engineered Net Shaping (LENS) method, with the starting material phase being powder-based. As there are many different orientations applicable to printing, it is thus important to find out which printing orientation would provide the most optimal mechanical properties. For this project, the mechanical property in question is the toughness of the metal. Therefore, this project aims to find out the most optimal printing orientation which would provide the toughest result, and the toughness test conducted will be the Charpy Impact Test. The microstructure of different printing orientations will also be studied to see the effect that different printing orientation has on the microstructure.